The Gender Mainstreaming Strategy as a Solution for the Constitutional Rights Violation of Female Circumcision - Lanny Ramli (Yuridika, 2022)
In recent years, violence against women has continued. Culture, beliefs, and the role of community and religious leaders are the reasons for the practice of female circumcision in East Java Province. To the perpetrators, this activity is reasonable. This article is a policy study with a gender perspective approach and uses qualitative methods and quantitative data. The results of this study reveal the insights of circumcision practitioners in women who are less aware of the effects of female circumcision, low education levels, and trust and pressure from the family (internal) and the environment (external). Moreover, the main rules are legalised as the 1945 Constitution explicitly outlines government interference in community control, including social and cultural. The gender mainstreaming strategy (PUG) has been implemented to eliminate activities that violate women's rights to health and other constitutional rights.